Application of Environmental Tracers in the Memphis Aquifer and Implication for Sustainability of Groundwater Resources in the Memphis Metropolitan Area, Tennessee. (December 2016) - Larsen, Daniel; Waldron, Brian; Schoefernacker, Scott; Gallo, Haley; Koban, John; Bradshaw, Elizabeth
Abstract: Fourteen years of results from environmental tracer sampling for 3 H, He isotopes, noble gases, and SF6 in production wells screened in the Memphis aquifer in Memphis, Tennessee, are presented and used to determine the age and mass proportion of modern water (<60 years old) pumped from this regionally important public supply aquifer. The results indicate persistent presence of modern water in water pumped from one or more production wells in most of the well fields sampled. The percentage of modern water is quantified by three methods: tritium‐loading history, inverse geochemical modeling, and lumped parameter modeling. The mixing percentages and ages determined from each technique are generally in agreement, but also emphasize the unique information provided by each tracer and associated modeling approaches. The implications of the tracer data for sustainability and vulnerability are also considered, especially in regard to potential water quality threats to the water supply in the Memphis, Tennessee, metropolitan area.